$\displaystyle \large \lim_{x \,\to\, a} \dfrac{x^n-a^n}{x-a}$ formula Proof

$x$ is a variable. $a$ and $n$ are constant. The limit of algebraic function $\dfrac{x^n-a^n}{x-a}$ as $x$ approaches $a$ is often appeared in calculus. So, this standard result can be used as a formula in limits to find the limit of algebraic functions.

$\displaystyle \large \lim_{x \,\to\, a} \normalsize \dfrac{x^n-a^n}{x-a}$

Now, let’s learn how to derive the proof to find the limit of this algebraic function as $x$ approaches $a$ in calculus.

Evaluate Limit by Direct Substitution method

Let’s find the limit of the algebraic function as $x$ approaches $a$ firstly.

$\displaystyle \large \lim_{x \,\to\, a}{\normalsize \dfrac{x^n-a^n}{x-a}} \,=\, \dfrac{a^n-a^n}{a-a}$

$\implies \displaystyle \large \lim_{x \,\to\, a} \normalsize \dfrac{x^n-a^n}{x-a} \,=\, \dfrac{0}{0}$

As $x$ tends to $a$, the limit of this algebraic function is indeterminate. So, let’s try another method to find the limit of this algebraic function.

Transform Limit of Algebraic function

If $x \,\to\, a$, then $x-a \,\to\, 0$.

$= \,\,\,$ $\displaystyle \large \lim_{x\,-\,a \,\to\, 0}{\normalsize \dfrac{x^n-a^n}{x-a}}$

Take $x-a = h$, then $x = a+h$. Now, eliminate the $x$ terms from the limit of the algebraic function.

$= \,\,\,$ $\displaystyle \large \lim_{h \,\to\, 0}{\normalsize \dfrac{{(a+h)}^n-a^n}{h}}$

The $n$-th power of $a$ is common in both terms of the numerator. So, it can be taken common from both terms for simplifying the numerator further.

$= \,\,\,$ $\displaystyle \large \lim_{h \,\to\, 0}{\normalsize \dfrac{a^n \Bigg[{\Bigg(1+\dfrac{h}{a}\Bigg)}^n-1 \Bigg]}{h}}$

Simplify the Algebraic function

The function ${\Bigg(1+\dfrac{h}{a}\Bigg)}^n$ is same as the Binomial Theorem. So, it can be expanded by the Binomial Theorem.

${\Bigg(1+\dfrac{h}{a}\Bigg)}^n$ $\,=\,$ $1$ $+$ $\dfrac{n}{1!} \dfrac{h}{a}$ $+$ $\dfrac{n(n-1)}{2!} {\Bigg(\dfrac{h}{a}\Bigg)}^2$ $+$ $\dfrac{n(n-1)(n-3)}{3!} {\Bigg(\dfrac{h}{a}\Bigg)}^3$ $+$ $\ldots$

$\implies$ ${\Bigg(1+\dfrac{h}{a}\Bigg)}^n-1$ $\,=\,$ $\dfrac{n}{1!} \dfrac{h}{a}$ $+$ $\dfrac{n(n-1)}{2!} {\Bigg(\dfrac{h}{a}\Bigg)}^2$ $+$ $\dfrac{n(n-1)(n-3)}{3!} {\Bigg(\dfrac{h}{a}\Bigg)}^3$ $+$ $\ldots$

$\implies$ ${\Bigg(1+\dfrac{h}{a}\Bigg)}^n-1$ $\,=\,$ $\dfrac{n}{1} \dfrac{h}{a}$ $+$ $\dfrac{n(n-1)}{2} {\Bigg(\dfrac{h}{a}\Bigg)}^2$ $+$ $\dfrac{n(n-1)(n-3)}{6} {\Bigg(\dfrac{h}{a}\Bigg)}^3$ $+$ $\ldots$

$\implies$ ${\Bigg(1+\dfrac{h}{a}\Bigg)}^n-1$ $\,=\,$ $n \times \dfrac{h}{a}$ $+$ $\dfrac{n(n-1)}{2} \times \dfrac{h^2}{a^2}$ $+$ $\dfrac{n(n-1)(n-3)}{6} \times \dfrac{h^3}{a^3}$ $+$ $\ldots$

$\implies$ ${\Bigg(1+\dfrac{h}{a}\Bigg)}^n-1$ $\,=\,$ $\dfrac{nh}{a}$ $+$ $\dfrac{n(n-1)h^2}{2a^2}$ $+$ $\dfrac{n(n-1)(n-3)h^3}{6a^3}$ $+$ $\ldots$

Now, substitute the expansion of the function in the limit of the algebraic function.

$\displaystyle \large \lim_{h \,\to\, 0}{\normalsize \dfrac{a^n \Bigg[{\Bigg(1+\dfrac{h}{a}\Bigg)}^n-1 \Bigg]}{h}}$ $\,=\,$ $\displaystyle \large \lim_{h \,\to\, 0}{\normalsize \dfrac{a^n \Bigg[ \dfrac{nh}{a} + \dfrac{n(n-1)h^2}{2a^2} + \dfrac{n(n-1)(n-3)h^3}{6a^3} + \ldots \Bigg]}{h}}$

$h$ is a common multiplying factor in each term of the numerator and there is also one $h$ term in the denominator. So, take $h$ common from all the terms of the numerator.

$= \,\,\,$ $\displaystyle \large \lim_{h \,\to\, 0} \normalsize \dfrac{a^n \times h \Bigg[\dfrac{n}{a} + \dfrac{n(n-1)h}{2a^2} + \dfrac{n(n-1)(n-3)h^2}{6a^3} + \cdots \Bigg]}{h}$

$\require{cancel} = \,\,\,$ $\displaystyle \large \lim_{h \,\to\, 0} \normalsize \dfrac{a^n \times \cancel{h} \Bigg[\dfrac{n}{a} + \dfrac{n(n-1)h}{2a^2} + \dfrac{n(n-1)(n-3)h^2}{6a^3} + \cdots \Bigg]}{\cancel{h}}$

$= \,\,\,$ $\displaystyle \large \lim_{h \,\to\, 0} \normalsize a^n \Bigg[\dfrac{n}{a} + \dfrac{n(n-1)h}{2a^2} + \dfrac{n(n-1)(n-3)h^2}{6a^3} + \cdots \Bigg]$

Find the Limit of the Algebraic function

It is time to evaluate the limit of the algebraic function as x approaches zero.

$= \,\,\,$ $a^n \Bigg[\dfrac{n}{a} + \dfrac{n(n-1)(0)}{2a^2} + \dfrac{n(n-1)(n-3){(0)}^2}{6a^3} + \ldots \Bigg]$

$= \,\,\,$ $a^n \Bigg[\dfrac{n}{a} + 0 + 0 + \ldots \Bigg]$

$= \,\,\,$ $a^n \times \dfrac{n}{a}$

$= \,\,\,$ $n \times \dfrac{a^n}{a}$

Use quotient rule of exponents to simplify the expression.

$= \,\,\,$ $n \times a^{n-1}$

$= \,\,\,$ $n.a^{n-1}$

$\,\,\, \therefore \,\,\,\,\,\, \displaystyle \large \lim_{x \,\to\, a} \large \dfrac{x^n-a^n}{x-a} \,=\, n.a^{n-1}$

Therefore, it is proved that the limit of the algebraic function as $x$ approaches $a$ is equal to $n$ times $a$ is raised to the power of $n-1$.

Email subscription
Math Doubts is a best place to learn mathematics and from basics to advanced scientific level for students, teachers and researchers. Know more
Follow us on Social Media
Math Problems

Learn how to solve easy to difficult mathematics problems of all topics in various methods with step by step process and also maths questions for practising.

Learn more